1941 nm Q-switched thulium-doped fiber laser with a multi-layer black phosphorus saturable absorber - Latiff, A.A.; Rusdi, M.F.M.; Jusoh, Z.; Yasin, M.; Ahmad, Harith; Harun, Sulaiman Wadi (INOE, 2016)
We demonstrate a Q-switched Thulium-doped fiber laser (TDFL) operating at 1941 nm region based on multi-layer black phosphorous (BP) as a saturable absorber (SA). The BP-based SA was prepared by mechanically exfoliating BP crystal and fixing the acquired BP flakes onto the scotch tape. A small piece of the tape was then sandwiched between two ferrules and incorporated in TDFL cavity to achieve stable Q-switched operation in conjunction with 1552 nm core pumping. The pulse repetition rate of the laser could be varied from 15.32 to 27.82 kHz, by tuning the pump power from 495 to 645 mW. At 645 mW pump power, the laser showed the average output power, pulse energy, and pulse width of 14 mW, 0.50 μJ, and 4.38 µs, respectively. Our results show that multi-layer BP is a promising SA for Q-switching laser operation in 2-micron region.